2014
DOI: 10.1371/journal.pone.0095163
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling and Physiological Studies Reveal a Major Role for Aromatic Amino Acids in Mercury Stress Tolerance in Rice Seedlings

Abstract: Mercury (Hg) is a serious environmental pollution threat to the planet. The accumulation of Hg in plants disrupts many cellular-level functions and inhibits growth and development, but the mechanism is not fully understood. To gain more insight into the cellular response to Hg, we performed a large-scale analysis of the rice transcriptome during Hg stress. Genes induced with short-term exposure represented functional categories of cell-wall formation, chemical detoxification, secondary metabolism, signal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 56 publications
4
48
0
Order By: Relevance
“…Phenylalanine, tyrosine, and tryptophan are essential components of proteins and precursors for various secondary metabolites that influence plant growth (Tzin and Galili 2010). Chen et al (2014) found that aromatic amino acids play important roles in confronting mercury (Hg) stress in rice seedlings. The phosphatidylinositol signaling system and the inositol phosphate metabolism pathway are also known to be involved in stress resistance.…”
Section: Transcriptome Analysis Of the Cold-tolerant Varietymentioning
confidence: 99%
“…Phenylalanine, tyrosine, and tryptophan are essential components of proteins and precursors for various secondary metabolites that influence plant growth (Tzin and Galili 2010). Chen et al (2014) found that aromatic amino acids play important roles in confronting mercury (Hg) stress in rice seedlings. The phosphatidylinositol signaling system and the inositol phosphate metabolism pathway are also known to be involved in stress resistance.…”
Section: Transcriptome Analysis Of the Cold-tolerant Varietymentioning
confidence: 99%
“…Activity of ACS increased in B. juncea plants exposed to Cd (Asgher et al, 2014 ), Ni or Zn (Khan and Khan, 2014 ), as well as in Cd-exposed T. aestivum plants (Khan et al, 2015 ). Transcript levels of ACS and ACO genes were rapidly enhanced in Cu-exposed B. oleracea (Jakubowicz et al, 2010 ), Al-exposed A. thaliana (Sun et al, 2010 ), chromium (Cr)-exposed Oryza sativa (Trinh et al, 2014 ), and Hg-treated O. sativa (Chen et al, 2014 ) and M. sativa plants (Montero-Palmero et al, 2014a ). In addition, Cd was shown to enhance ACS gene expression in G. max (Chmielowska-Bąk et al, 2013 ) and ACS and/or ACO transcription in H. vulgare (Cao et al, 2014 ), O. sativa (Trinh et al, 2014 ) and A. thaliana plants (Herbette et al, 2006 ; Weber et al, 2006 ; Schellingen et al, 2014 ; Table 1 ).…”
Section: Metal Stress Affects Ethylene Biosynthesis and Signaling At mentioning
confidence: 99%
“…Recently, a whole-genome transcriptional profile from M. sativa seedlings exposed to 3 μM Hg for 3, 6 and 24 h demonstrated significant upregulation of several ethylene-responsive genes such as ERF1 , mostly during the earliest hours of exposure (Montero-Palmero et al, 2014a ). Similarly, Hg exposure affected genes related to ethylene signaling in M. truncatula (Zhou et al, 2013 ), O. sativa (Chen et al, 2014 ), H. vulgare plants (Lopes et al, 2013 ). Furthermore, roots of O. sativa plants exposed to 200 μM Cr for up to 3 h showed an increased expression of the EIN3;4 gene (Trinh et al, 2014 ), while the EIN2 gene was induced in Pb-exposed A. thaliana plants (Cao et al, 2009 ; Table 1 ).…”
Section: Metal Stress Affects Ethylene Biosynthesis and Signaling At mentioning
confidence: 99%
“…A total of eight previously published rice microarray data sets were downloaded from Gene Expression Omnibus database [(GSE IDs: GSE33375, GSE63152, GSE41719, GSE41733, GSE34899, GSE27413, and GSE34895) 1 ] ( Chi et al, 2011 , 2013 ; Huang et al, 2012 , 2014 ; Lin et al, 2013a , b ; Chen et al, 2014 ). Each data set was composed of three biological replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous works have revealed early molecular responses (1 and 3 h) of rice to individual rhizotoxins ( Chi et al, 2011 , 2013 ; Huang et al, 2012 , 2014 ; Lin et al, 2013a , b ; Chen et al, 2014 ). In the present study, we focused on the early GSR of rice by integrating previously published data.…”
Section: Introductionmentioning
confidence: 99%